The Hegetotheriidae (Mammalia, Notoungulata) assemblage from the late Oligocene of Mendoza, central-western Argentina - Cerdeño Serrano, Maria Esperanza (2015)
This study describes new remains of Hegetotheriidae (Notoungulata), including a new species, from the Deseadan (late Oligocene) of Quebrada Fiera, Mendoza Province, Argentina. The assemblage is composed of four hegetotheriines, Prohegetotherium cf. P. sculptum, Prohegetotherium sp., Prohegetotherium schiaffinoi, Prohegetotherium malalhuense sp. nov., and the pachyrukhine Propachyrucos cf. P. simpsoni. The presence of Prosotherium cannot be totally discarded as lower molariforms are rather similar between both pachyrukhine genera. The new species Prohegetotherium malalhuense sp. nov. differs from all previously described hegetotheriines by lingually projecting, sharp parastyle and marked parastyle groove on ectoloph of M2?3; talonid of m1?m2 posterolabially projected; talonid of m3 with marked posterolabial groove; and smaller size. Its phylogenetic affinities are not well resolved; Prohegetotherium results paraphyletic, with P. sculptum as sister taxon of the remaining hegetotheres, and the new taxon more related to Hegetotherium mirabile than to P. schiaffinoi. The recognition of P. schiaffinoi and Prohegetotherium cf. P. sculptum emphasizes that the fauna from Quebrada Fiera shares elements with roughly contemporaneous Deseadan faunas from northern and southern latitudes, but important faunal particularities distinguish the region as well. The record of pachyrukhines at Quebrada Fiera more closely resembles Deseadan faunas in Patagonia than temporally correlative faunas from Bolivia and Uruguay, and indicates the presence of suitable habitats in mid-latitudes of Argentina for this hypselodont clade. Faunal affinities together with particular taxa from Quebrada Fiera seem to support a significant faunal provinciality in South America during the late Oligocene.